Multi-omics analyses of radiation survivors identify radioprotective microbes and metabolites - Guo, Hao; Chou, Wei-Chun; Lai, Yunjia; Liang, Kaixin; Tam, Jason W.; Brickey, W. June; Chen, Liang; Montgomery, Nathan D.; Li, Xin; Bohannon, Lauren M.; Sung, Anthony D.; Chao, Nelson J.; et al. (Science (American Association for the Advancement of Science), 2020)
A common symptom of radiation treatment for cancer is gastrointestinal disruption. The damage caused can become so severe and debilitating that it interrupts treatment. Guo et al. noticed that mice surviving experimental radiation exposure had distinctive taxonomic representation in their gut microbiota. A similar correlation was also observed in a small group of human subjects. Further experiments in mice revealed that some strains of bacteria produced high levels of short-chain fatty acids, which seemed to be dampening inflammatory responses and alleviating the damage caused by reactive oxygen species released by the radiation. A metabolomics analysis also implicated a role for tryptophan metabolic pathways in radiation survivorship. Science , this issue p. eaay9097 Certain families of gut microbes appear to enhance host mouse survival responses to radiation damage. Ionizing radiation causes acute radiation syndrome, which leads to hematopoietic, gastrointestinal, and cerebrovascular injuries. We investigated a population of mice that recovered from high-dose radiation to live normal life spans. These “elite-survivors” harbored distinct gut microbiota that developed after radiation and protected against radiation-induced damage and death in both germ-free and conventionally housed recipients. Elevated abundances of members of the bacterial taxa Lachnospiraceae and Enterococcaceae were associated with postradiation restoration of hematopoiesis and gastrointestinal repair. These bacteria were also found to be more abundant in leukemia patients undergoing radiotherapy, who also displayed milder gastrointestinal dysfunction. In our study in mice, metabolomics revealed increased fecal concentrations of microbially derived propionate and tryptophan metabolites in elite-survivors. The administration of these metabolites caused long-term radioprotection, mitigation of hematopoietic and gastrointestinal syndromes, and a reduction in proinflammatory responses.